Movimentos de tronco em Libras na produção poética de Isabel Alvim: a construção de sentidos em análise - Lima, Maria Aparecida Marques de (2024)
This study analyzes the production of meaning in a verbo-visual text in Brazilian Sign Language (Libras) in Isabel Alvim's poem "March 8: International Women's Day," focusing on the trunk movement used in the signaling. The theoretical approaches are based on Bakhtin's studies (2008) and Brait's verbo-visuality (2009; 2013). The objectives stem from the following research question: How is dialogism configured in Isabel Alvim's work "March 8: International Women's Day"? The general objective was: a dialogic analysis of Isabel Alvim's work "March 8: International Women's Day." The specific objectives were: to understand the sphere and discursive genre and the authorship of the text, to examine the theme of the poem in its sociocultural context, to investigate the production of meanings of the verbo-visual text that emerges from the trunk movement present in the signing produced in the deaf poetry; to examine the role that trunk movement plays in the production of meanings within the signing and to verify if verbo-visuality is a constituent of the sign through trunk movement. We adopted a qualitative documentary methodology to analyze the production of meaning in the verbo-visual text "International Women's Day," produced in video by the poet Isabel Alvim, in which the researcher adopted sign writing for systematization, organization, visualization, and recording of the trunk movement to be analyzed. Analyzing the sociocultural aspects present, which, in turn, are composed of imagetic resources linked to the cultural reality of the deaf subject in the investigation of the poetry. The analysis followed several axes: Sphere and Discursive Genre: The work in question is identified as belonging to the literary genre, using the poetic form to explore the theme. Deaf poetry, typically signed, stands out for its artistic and literary expression that emerges from the deaf community, incorporating visual and spatial elements (Sutton-Spence, 2021). Authorship: Isabel Alvim reveals her deaf identity by incorporating the "deaf self" into her poem. Although she addresses the theme of women, the poetic self identifies as deaf, recognizing herself as a deaf woman in the work. Thus, the authorial self merges with the poetic self. Theme of the Poem: Isabel Alvim's poem celebrates International Women's Day, highlighting women's experiences, struggles, and achievements throughout history. Analysis of Trunk Movement and Its Effects on Meaning: The trunk movements in Libras signaling help us understand and interpret the signs more fully, considering the nuances and intentions conveyed by these movements. This allows us to appreciate the richness and complexity of this language as a means of communication and artistic expression. The research results show that trunk movement is configured as a crucial element in differentiating the meaning of a sign, as it allows for the presentation of the intensity of a movement, as well as the sense and meaning generated within the signaling, always respecting the historical-cultural context. For example, one of the most striking senses that trunk movement adds to the discourse is emphasis, highlighting signs and intensifying emotions.